Membangun Karakter Optimisme dan Menghindari Putus Asa dalam Al-Qur’an serta Hubungannya dengan Krisis Mental - Fadwa Nabilah; Sahdin Hasibuan (CV Global Research Publication, 2026)
Mental crisis has become one of the serious issues in modern society, particularly among the younger generation, due to academic, social, and economic pressures, as well as the influence of social media, which may trigger stress, anxiety, depression, burnout, and loss of hope in life. This study aims to examine how the Qur’an builds the character of optimism and prohibits despair as a spiritual and psychological response to mental crisis. This study employs a qualitative method with a library research design and a thematic interpretation approach. The primary data are derived from Qur’anic verses related to optimism and the prohibition of despair, namely QS. Al-Baqarah: 286, QS. Al-Insyirah: 5–6, QS. Yusuf: 87, and QS. Fussilat: 49, supported by Tafsir At-Thabari, Tafsir Al-Mishbah, and Tafsir Al-Azhar as the main exegetical references. The findings show that the Qur’an offers psychological and spiritual guidance through the values of patience, tawakal, gratitude, remembrance of Allah, belief in Allah’s mercy, and hope for ease after hardship. Optimism in the Qur’an functions as a foundation for strengthening life motivation and mental resilience, while the prohibition of despair serves as emotional protection so that humans do not become trapped in adversity. Thus, Qur’anic teachings are relevant as a spiritual framework for building mental health and overcoming psychological crises in the contemporary era.